(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
The acquisition of specialized tourism terminology is a critical component of communicative competence for learners and professionals in the hospitality industry. Recent advances in information technology (IT) offer innovative pedagogical approaches that enhance terminology learning through interactive multimedia, mobile applications, and corpus-based tools. This review critically examines empirical studies published between 2015 and 2024, highlighting the efficacy of digital flashcards, virtual reality simulations, and adaptive learning platforms in promoting retention and contextual usage of tourism vocabulary. We analyze the integration of concordancers and authentic online corpora to foster learner autonomy, while considering the role of gamification and social networking features in increasing motivation and engagement. Additionally, challenges such as digital literacy disparities and resource accessibility are discussed. The synthesis of current evidence informs best practices and future research directions, emphasizing the need for interdisciplinary collaboration among linguists, educators, and IT developers to optimize technology-enhanced terminology instruction in tourism education.